Analisis citra landsat untuk mengestimasi potensi karbon Di atas permukaan tanah di kawasan hutan pendidikan Universitas tadulako - Misra, . (Universitas Tadulako, 2018)
Information of aboveground carbon stock can be obtained convensionally, which request cost, power, and time. That is necessary to acquire technologi of remote sensing and global information system (GIS). The objectives are to estimate potency and distribution aboveground carbon stock using landsat 7 ETM image in forest education of Tadulako University. The research method is supervised classification, normalized vegetation indeks (NDVI), field measurement (dbh), and alometric equation to estimate biomass. The study result showed that total aboveground carbon stock was 751.400, 26 ton. 377.286,53 ton in primary forest, 364.241,27 ton in secondary forest, 715,10 ton in scrubs and 9.157,37 ton in mixed farms. Keywords : Aboveground Carbon Stock, Landsat 7 ETM image, Forest education